Hepatitis C Among Injecting Drug Users Is Two Times Higher in Stockholm, Sweden than in Rotterdam, the Netherlands. (6th December 2013) - Norden, Lillebil; van Veen, Maaike; Lidman, Christer; Todorov, Ivo; Guarita, Bruno; Kretzschmar, Mirjam; Wiessing, Lucas
<x xml:space="preserve">Abstract</x> This study assessed risk behavior and preventive measures for hepatitis C among injecting drug users in Rotterdam, the Netherlands (452 participants, 2002–2003) and Stockholm, Sweden (310 participants, 2004–2006), two cities with contrasting drug policies. Uni- and multivariate logistic regression models were used. We found that the prevalence of hepatitis C was almost two times higher in participants from Stockholm than in participants from Rotterdam, even after adjustment for sex sharing paraphernalia (adjusted relative risk: 1.92, 95% confidence interval: 1.60–2.29). Follow-up comparative studies are needed to determine if policies with structured health programs can decrease transmission of hepatitis C.